2020
DOI: 10.1093/jcde/qwaa041
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal vibration of carbon/boron-nitride nano-hetero-structure in thermal and magnetic fields by means of nonlinear finite element method

Abstract: Hybrid nanotubes composed of carbon and boron-nitride nanotubes have manifested as innovative building blocks to exploit the exceptional features of both structures simultaneously. On the other hand, by mixing with other types of materials, the fabrication of relatively large nanotubes would be feasible in the case of macroscale applications. In the current article, a nonlinear finite element formulation is employed to deal with the nonlocal vibrational behavior of carbon/boron-nitride nano-hetero-tubes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…As a result, at smaller deflection values, there may be no need to adopt the higher-order non-local strain gradient theories [60]. Sedighi et al [61] simultaneously considered the impacts of length ratio, size dependence, magnetic field, and temperature environment on the nonlinear vibrational properties of composite CNT/BNNT. Figure 4 depicts a doubly clamped nano-heterostructure composed of two different types of tubular materials.…”
Section: Thermal Vibration Of Nanotubementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, at smaller deflection values, there may be no need to adopt the higher-order non-local strain gradient theories [60]. Sedighi et al [61] simultaneously considered the impacts of length ratio, size dependence, magnetic field, and temperature environment on the nonlinear vibrational properties of composite CNT/BNNT. Figure 4 depicts a doubly clamped nano-heterostructure composed of two different types of tubular materials.…”
Section: Thermal Vibration Of Nanotubementioning
confidence: 99%
“…As a result, the effect of the magneto-thermal environment is also considered while investigating the vibration characteristics of such composite structures. Sedighi et al [61] demonstrated that when the contribution of the boron-nitride section is dominant, the location of the greatest amplitude would shift to the left when considering larger temperature gradients. In addition, they found that the configurations of the non-linear mode forms are substantially influenced by the high-temperature environment.…”
Section: Thermal Vibration Of Nanotubementioning
confidence: 99%
“…The studies on the static and dynamic analyses with nonlocal elasticity of beams [31][32][33][34][35][36][37][38][39][40][41][42][43][44] and rods [45][46][47][48][49][50][51] have led to an understanding of the mechanical behaviors of atomic-scaled structures. Moreover, the thermal vibration 52 and buckling 53 of Euler-Bernoulli beams, thermal vibrations of Timoshenko beams, 54,55 and vibration of Rayleigh beam axially loading and lying on two-parameter elastic foundation 56 are studied.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale devices [1][2][3][4], biological and bioinspired materials [5][6][7], advanced porous nanostructures [8,9], self-healing matter [10], hierarchical and periodic structures [11,12], new-generation of complex composites [13][14][15] require sophisticated methodologies and advanced models to predict their mechanical behavior. Usually, classical models of local continuum elasticity are not accurate enough to simulate the mechanical behavior of these nonconventional structural elements.…”
Section: Introductionmentioning
confidence: 99%